Assessment of a Self-regulated Learning Intervention. (2014) - González-Pienda, Julio A.; Fernández, Estrella; Bernardo, Ana; Núñez, José C.; Rosário, Pedro
Abstract Following a pretest-posttest design with no control group, this paper evaluates the efficacy of an intervention program. Consisting of twelve sessions, the program endeavored to increase knowledge and use of self-regulated learning strategies, as well as study time, in 277 first-year students in the Spanish secondary education system. The intervention’s efficacy was assessed in terms of three variables: knowledge of self-regulated learning strategies, use of self-regulated learning strategies, and study time. The results of post-intervention data analysis indicate that statistically significant changes occurred in students’ knowledge of self-regulated learning strategies and weekly study time, but not in their use of self-regulated learning strategies. When the sample was stratified into three groups (high, moderate, and low) according to baseline scores on the dependent variables, our findings show that students in the lower group profited most from the intervention on all three variables. This suggests that participation in the program is especially useful for at-risk students (i.e. those with little knowledge and use of effective learning strategies).